2018
DOI: 10.1163/15685306-12341473
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Factors in Companion Animal Relinquishment on the Sunshine Coast, Australia

Abstract: There is a critical need to reduce the surrender rates of companion animals by understanding the socioeconomic circumstances of caretakers. This research analyzed questionnaires with 117 relinquishers and 13 interviews. Interviews were conducted with relinquishers and staff at Sunshine Coast Animal Refuge Society and Sunshine Coast Animal Pound. Most companion animals relinquished were from litters and around half were de-sexed and micro-chipped. A caretaker's living situation was a critical reason for relinqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…Strong attachment bonds to pets are considered to be protective against shelter relinquishment [ 45 ]; however, socioeconomic factors can often make relinquishment unavoidable [ 46 ]. In particular, the U.S. has a shortage of affordable, pet-friendly housing, as pet fees and restrictions are unregulated [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strong attachment bonds to pets are considered to be protective against shelter relinquishment [ 45 ]; however, socioeconomic factors can often make relinquishment unavoidable [ 46 ]. In particular, the U.S. has a shortage of affordable, pet-friendly housing, as pet fees and restrictions are unregulated [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respondents' lack of acceptance of strategies that cause dog and cat deaths directly due to human intervention may be influenced by the knowledge that human activities are perhaps the greatest threat to wildlife and so want to avoid 'blaming' companion species, and by the concept that humans should at least allow wild dogs and cats to live a 'natural' life given that humans introduced these species to the wildlife habitat. This may be associated with the point that we have entered into the sixth mass extinction caused by humans [73,74], and the need to tailor management actions to the underpinning socio-economic values of places with place-based solutions [58,75].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that, given the breadth of perspectives, there are opportunities to strategically design management actions for either reducing or preventing wild dog and cat predation on wildlife and controlling domesticated (owned) dogs and cats tailored to more specific contexts [61]. The fact that the differences between gender and age groups in attitudes towards dog and cat control are determined by dominant societal and cultural values may mean that managers could better focus their attention on designing strategies tailored to specific localities where cultural and place-based factors tend to condition gender, age, and pet-ownership norms and thus attitudes and regulations [75]. Considering the uncertainties of the different environmental variables (e.g., the predominant wildlife species being protected and social and ecological characteristics of the site), practical factors (e.g., social, cultural, and financial factors and constraints), and the receptivity of local communities to various management strategies and options, designing strategies tailored to specific localities could have greater and more sustained success than generic strategies applied across all localities.…”
Section: Discussionmentioning
confidence: 99%
“…Another inconclusive finding was that the difference in socioeconomic levels between reported cases citing and not citing abandonment was small. Dog ownership is positively correlated to household income [30,42,52]. However, it has been suggested that people with lower household income are less likely to relinquish their dogs, for financial reasons [14].…”
Section: Discussionmentioning
confidence: 99%
“…Among all these risk factors, the role of household socioeconomic level in crimes and animal welfare concerns is not yet well understood [6,20,22]. It has been proposed that socioeconomic status is negatively correlated with the frequency of crimes, domestic violence, and neglecting and abusing animals [6,22,29,30,31]. However, a tautologous relationship has also been postulated, because a dog owner’s socioeconomic status may affect his or her ability to provide for all aspects of good welfare.…”
Section: Introductionmentioning
confidence: 99%